2008
DOI: 10.5664/jcsm.27283
|View full text |Cite
|
Sign up to set email alerts
|

Signs of Insomnia in Borderline Personality Disorder Individuals

Abstract: Scientific inveStigAtionSStudy objectives: Recent findings suggest few differences in sleep continuity and quality between borderline personality disorder individuals (BPD-I) and good sleepers (GS). Nonetheless, BPD-I show marked discrepancies between subjective and objective sleep measures. The objective of this study was to document sleep in BPD-I, GS, and insomnia sufferers (paradoxical, Para-I; psychophysiological, Psy-I). Participants: Twelve BPD-I (mean age 33.3 years), 15 GS (mean age 34.1 years), 15 Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…Nevertheless, recent studies have found elevated levels of SWS sleep in BPD patients (Bastien et al, 2008) and increased spectral delta power in NREM sleep (Philipsen et al, 2005). We suggest that these novel findings are due to the better control of co-morbid psychopathology and to the change in the psychiatric consensus focusing more on the "impulsivity" dimension of BPD (Zanarini, 1993).…”
Section: Main Findingsmentioning
confidence: 67%
See 1 more Smart Citation
“…Nevertheless, recent studies have found elevated levels of SWS sleep in BPD patients (Bastien et al, 2008) and increased spectral delta power in NREM sleep (Philipsen et al, 2005). We suggest that these novel findings are due to the better control of co-morbid psychopathology and to the change in the psychiatric consensus focusing more on the "impulsivity" dimension of BPD (Zanarini, 1993).…”
Section: Main Findingsmentioning
confidence: 67%
“…A "NEGLECTED" SYMPTOM: DISTURBED SLEEP IN BPD Subjective sleep difficulties are often reported in BPD (Bastien, Guimond, St-Jean & Lemelin, 2008;Philipsen, Feige, Al-Shajlawi et al, 2005) and different lines of research suggest that altered sleep architectureas evidenced by polysomnographic measuresis a common characteristic of this mental disorder (Boutros, Torello & McGlashan 2003). Nevertheless, relatively few studies investigated the specific sleep profile in BPD.…”
Section: The Psychopathological Profile Of Borderline Personality Dismentioning
confidence: 99%
“…A perception of poor sleep quality in the absence of objectively-measured poor sleep is not unique to severe PMS. Similarly, research has shown that patients with irritable bowel syndrome (Elsenbruch et al, 2002), borderline personality disorder (Bastien et al, 2008;Philipsen et al, 2005) and insomnia (Harvey and Tang, 2012;Krystal and Edinger, 2008) may report poor sleep quality in the absence of objective sleep disturbances. In pregnant and postpartum women, subjective and actigraphy measures of sleep efficiency are not correlated and there is a strong association between poor subjective nighttime sleep, but not objective sleep, and greater psychological disturbances (Bei et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These altered sleep responses may relate to the circadian rhythm disturbances that characterize this population (reviewed in Shechter and Boivin, 2010). Interestingly, patients with borderline personality disorder have higher delta power (Philipsen et al, 2005) or more Stage 4 sleep (Bastien et al, 2008) in addition to having poorer, non-refreshing sleep and feeling fatigued upon awakening. Women with severe PMS or PMDD also have distinct personality traits, particularly higher neuroticismrelated traits, such as trait-anxiety and stress susceptibility (Halbreich, 1997), and they are more likely to have traits of a personality disorder, particularly obsessive-compulsive disorder (Sassoon et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation